Work fatigue and physiological symptoms in different occupations of high-elevation construction workers / Mohamad Arif Muahzim - Mohamad Arif, Muahzim (2018)
The objectives of this study are to evaluate common work fatigue symptoms and also evaluate differences of physiological strain among construction workers. Total of 60 workers are divided into two groups which are high elevated construction workers and ground level construction workers. Questionnaires consisting demographic data and subjective work fatigue symptoms were distributed and there are also physiological measurement such as heart rate have been collected. Workers required to wear Vivosmart 3 on their wrist for heart rate measurements. Prior to performing measurements, a study found that most of the construction workers have enough sleep time between 7 hours to 9 hours. This could be explained by eliminating those ftigue workers before performing the experimental measurements. For subjective work fatigue symptoms, feel pain in the waist is the most common work fatigue symptoms with prevalence rate for high elevated construction workers and ground level construction workers are 80% and 100% respectively. It can lead to work musculoskeletal disorder that can affect productivity and performance of the workers. The high level construction workers have higher heart rate readings compared with those among ground level construction workers. This indicates that high elevation construction workers have higher physiological strain. This study shows that the subjective fatigue symptoms questionnaires can be used to measure fatigue prevalence and heart rate is a suitable physiological measurement to evaluate physiological strain that construction workers encounter.